Parental circumstances leading to child sexual abuse in Zimbabwe - Muridzo, Noel G.; Chikadzi, V.; Mafa, Itai; Chinyenze, P. (Journal of Social Development in Africa, 2021)
Child sexual abuse remains one of the leading social ills of our time. It is a phenomenon that has multi-faceted consequences on children, families and the society at large. This paper discusses findings emanating from a study which explored the phenomenon of child sexual abuse in Zimbabwe. Using a qualitative approach and a case study design, the study discusses how parental circumstances are key factors that lead to the vulnerability of children to sexual abuse. The authors call for a paradigm shift from curative social welfare services in dealing with child sexual abuse, and advocate for a preventative-oriented practice that addresses macro-ecological factors that contribute to vulnerability of children to sexual abuse.